Un modèle analytique des transferts de technologie - Henner, Henri-F. (L'Actualité économique)

(untitled) (HEC Montréal, 1984)
ABSTRACTThis study deals with international technology transfers. A theoretical and analytical model is presented as well as applications to real international economic problems. In the first part the author reminds the Ricardian model with a continuous of goods. In the second part, the model is applied to the study of technology transfers and an attempt is made to deal with endogeneous technological change using Pugel's approach. In the last part, the model is applied to the following questions: free technology transfer, the choice of an appropriate technology, the relation between wage rate and technology transfers.